Single and repetitive paired-pulse suppression: does it provide an analysis of synaptic inhibition in epilepsy research? - Waldbaum, Simon, author; Dudek, F. Edward, advisor; Partin, Kathryn M., committee member; Garrity, Deborah, committee member; Handa, Robert J., committee member (Colorado State University. Libraries, 2007)
The paired-pulse technique has a long history of use in neurophysiological studies in the hippocampus, particularly in epilepsy research where it has been a convenient but indirect measure of synaptic inhibition. Most investigators have used a single paired-pulse protocol, while others have utilized repetitive paired pulses. Nearly all of the electrophysiological evidence that inhibition is increased after synaptic reorganization in the hippocampus derives from this technique. This study investigated the dependence of single and repetitive paired-pulse suppression on stimulus parameters and levels of membrane excitability in the perforant path-granule cell network. The hypothesis was tested that slightly reduced GABAA-receptor mediated inhibition results in an increase in paired-pulse suppression. Single paired-pulse suppression was analyzed as a function of stimulus intensity and interpulse interval with field-potential recordings from the granule cell layer and stimulation of the perforant path. Six different interpulse intervals (20-200 ms) were used at stimulus intensities that evoked responses ranging from 25% to 100% (i.e., the maximum). Paired-pulse suppression during a repetitive train of 10 paired pulses was analyzed as a function of stimulation intensity, interpulse interval and frequencies of 0.1-4.0 Hz. Stimulation intensities of 75% to 100% of maximum resulted in a higher degree of paired-pulse suppression, as did interpulse intervals from 20-60 ms. At lower frequencies, single and repetitive paired-pulse protocols yielded similar levels of paired-pulse suppression. The degree of paired-pulse suppression, however, depended heavily on the interplay of stimulation intensity, interpulse interval and stimulus frequency, particularly when repetitive paired pulses were given at higher frequencies. The amplitude of the population spike produced by the conditioning pulse progressively increased during stimulation at higher frequencies (1.0-4.0 Hz). Alterations in ionic conditions from 3.0 to 6.0 mM [K+] and from 1.0 to 2.5 mM [Ca++] showed that paired-pulse suppression was maximal when membrane excitability was highest. Under physiological ionic conditions, increased levels of paired-pulse suppression were measured during bath application of the GABAA-receptor antagonist SR-95531, which reduced GABAA-receptor mediated inhibition. Therefore, the paired-pulse technique erroneously measured increased rather than decreased levels of "inhibition" under conditions of slightly increased excitability. These results indicate that the paired-pulse technique is not a reliable or accurate measure of synaptic inhibition, and strongly challenges the electrophysiological evidence supporting the "hyperinhibition" hypothesis after epilepsy-associated synaptic reorganization in the hippocampus.
Keywords: neurosciences